Lucinda's secret - DiTerlizzi, Tony; Black, Holly (New York : Simon and Schuster Books for Young Reader, 2003)
With goblins, trolls, and the house boggart all trying to get them, the Grace children turn to Great Aunt Lucinda for help.
Keywords: Siblings -- Juvenile fiction; Fantasy fiction